Representação colaborativa de imagens em ambientes digitais: estudo de iniciativas - Santos, Maria Luiza da Silva Correa dos (Universidade Federal de São Carlos, 2021)
The large production of data and information in the digital environment experienced in recent decades requires from Information Science a set of theories and practices that ensure ways to organize, represent and make available, for the purposes of access and retrieval, the various types of informational and digital objects. In this regard, the relevance of the thematic representation of these materials grows, highlighting the growing number of platforms and digital environments that make use of the experiences and specialized knowledge of their users for a collaborative work of content representation. In this direction, this research questions the best practices for the collaborative representation of images in digital environments. As a way of contributing to this discussion, the objective is to analyze the practices of image representation in a folksonomic context included in the specialized literature of Library Science and Information Science, having as object of investigation the national publications conducted on the subject. Therefore, an exploratory and bibliographic research with a quali-quantitative approach was carried out, with the collection and analysis of eighteen documents collected in the BRAPCI and BDTD databases. For a better visualization of the results, a summary table of the practices and platforms used is presented, in addition to the classification of these practices into four categories that group them according to their similarities. It is observed that the main initiatives for collaborative representation of images in digital environments are: analysis of labeling quality and user behavior; analysis and comparative evaluation between the social indexing of a collaborative system and methodologies of analysis and indexing of Information Science images; and union of collaborative indexing with Knowledge Organization Systems. It was also found that Flickr is the platform most frequently used by these initiatives. It is concluded that there are several initiatives of collaborative representation of images in a folksonomic context worked on by the national literature and, although there are similarities between the practices within the same category, they have specific characteristics. It is recommended that further practical research focus on exploring the potential of folksonomy in the representation of images in digital environments from the blending of elements of traditional indexing with elements of collaborative representation in contemporary digital environments.
Collaborative representation of images in digital environments: study of initiatives
Keywords: Folksonomia; Representação da informação; Informação imagética; Ambientes digitais; Ciência da Informação; Folksonomy; Information representation; Imagery information; Digital environments; Science Information; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA